Carbon‐Quantum‐Dots‐Loaded Mesoporous Silica Nanocarriers with pH‐Switchable Zwitterionic Surface and Enzyme‐Responsive Pore‐Cap for Targeted Imaging and Drug Delivery to Tumor. Issue 12 (14th March 2016) - Liu, Zhongning; Chen, Xin; Zhang, Xiaojin; Gooding, John Justin; Zhou, Yongsheng
Abstract : Mesoporous silica nanocarriers with pH‐switchable antifouling zwitterionic surface, enzyme responsive drug release properties and blue fluorescence are reported. Prolonged circulation in the blood system with zero premature release as well as efficient cellular uptake and intracellular drug release in tumor tissue are achieved.